Evaluasi Penerimaan Modul Kepegawaian SIESTA Menggunakan Model Utaut2 - Supriyanto, Shafira Rahmi; Rolliawati, Dwi; Yalina, Nita (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
The successful application of information technology largely depends on the level of acceptance of each user. Therefore, accurate interpretation and estimation are needed so that user acceptance can be increased. This also happened to SIESTA, which until now has never been examined the acceptance of the system. The purpose of this study is to be able to understand aspects that have an influence on the acceptance of the modul Kepegawaian SIESTA with the UTAUT2 model up to the RSUD Dr. Soetomo Surabaya can utilize the results of research in implementing other SIESTA modules. The sampling technique was determined by the disproportionate stratified random sampling technique and the sample size used was 359. The analysis of the data and the results of the SEM-PLS hypothesis test prove that behavioral intention is significantly influenced by social influence and price value aspects. While aspects of facilitating conditions and habits have a significant impact on aspects of use behavior. There are no aspects of moderator age, gender, and experience that meet significant criteria. Then it can be seen that age, gender, and years of service do not strengthen the influence of core aspects on the acceptance of the modul Kepegawaian SIESTA